Modelling and experimental validation of heat transfer behavior during trans-critical transients. (15th June 2023) - Song, Meiqi; Liu, Xiaojing; Cheng, Xu
Highlights: Supercritical power cycles may experience trans-critical procedures during start-up, shut down, or accident condition. The thermal–hydraulic code has been upgraded for simulation of trans-critical transients. A calibration model to IAFB heat transfer correlation at the near critical pressure condition has been developed. The modified code gets well validated by trans-critical experiments. Abstract: Though designed to be operated in supercritical conditions, supercritical power systems could experience trans-critical transients in which the pressure transfers between supercritical and subcritical condition during startup, shutdown, or accident condition. In the present work the thermal–hydraulic code ATHLET-SC was upgraded to predict the heat transfer behavior during trans-critical procedures. Prediction model of dispersed droplet flow film boiling (DFFB) heat transfer correlation, critical heat flux (CHF) correlation, and the correlation of minimum film boiling temperature T MFB has been upgraded. It is demonstrated by the validation work that the prediction error is large in the inverted annular film boiling (IAFB) regime. However, steady-state IAFB heat transfer experiment at high-pressure condition is unavailable. Hence, a calibration approach to IAFB heat transfer correlation is developed based on trans-critical transient experiment. As validated, the change of the wall temperature during the trans-critical transient gets well predicted by the corrected Bromley correlation.